A study of the elective franchise in the United States - Copley, Mary (My University, 1906)
Introduction: The question of franchise has ever held an important position in the minds of the American people. From the very outset of our colonial times we see the people entertaining the idea of limited suffrage. And it is here also that we see the development of that prominent yet valuable feature of our present government, the differences in qualifications and disqualifications among the various local and state elections. The elective franchise of America does not necessitate the casting of a vote by every member of a community, in fact this would be a greater detriment and a benefit to our great nation. According to Mr. Hart’s book on Actual Government we find disqualifications classed under four heads namely: (1) Persons of Real or Supposed Incapacity. This includes children until they become of age, the insane, and persons in confinements. (2) Persons Temporarily Disqualified. This class consists chiefly in requiring persons to live in the state, county, or district in which they wish to cast their vote a certain prescribed time. (3) Material Qualification. The qualifications included under this head are two in number; the holding of real estate or personal property and the paying of taxes. (4) Moral and Intellectual Qualification. Persons convicted of crime, or guilty of giving or receiving bribes are excluded from voting this head. Further those that believe in Polygamy or that can not read or write are excluded by means of their violating this requirement. The exclusion of women from the polls has been contrary to these laws just laid down, and consequently has opened much discussion.
Citation: Copley, Mary. A study of the elective franchise in the United States. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Elective Franchise; United States; Elections; Theses; Manuscripts (documents)